Comparative Pharmacokinetics of Levofloxacin in Healthy and Renal Damaged Muscovy Ducks following Intravenous and Oral Administration - Mohamed Aboubakr; Ahmed Soliman (Veterinary Medicine International)
The pharmacokinetics aspects of levofloxacin were studied in healthy and experimentally renal damaged Muscovy ducks after single intravenous (IV) and oral (PO) dose of 10 mg kg−1 bwt. Following IV administration, elimination half-life (t1/2(β)) and mean residence time (MRT) were longer in renal damaged ducks than in healthy ones. Total clearance (Cltot) in renal damaged ducks (0.20 L kg−1 h−1) was significantly lower as compared to that in healthy ones (0.41 L kg−1 h−1). Following PO administration, the peak serum concentration (Cmax) was higher in renal damaged than in healthy ducks and was achieved at maximum time (tmax) of 2.47 and 2.05 h, respectively. The drug was eliminated (t1/2(el)) at a significant slower rate (3.94 h) in renal damaged than in healthy ducks (2.89 h). The pharmacokinetic profile of levofloxacin is altered in renal damaged ducks due to the increased serum levofloxacin concentrations compared with that in clinically healthy ducks. Oral administration of levofloxacin at 10 mg kg−1 bwt may be highly efficacious against susceptible bacteria in ducks. Also, the dose of levofloxacin should be reduced in renal damaged ducks. Pharmacokinetic/pharmacodynamic integration revealed significantly higher values for Cmax/MIC and AUC/MIC ratios in renal damaged ducks than in healthy ones, indicating the excellent pharmacokinetic characteristics of levofloxacin in renal damaged ducks.